Waerdeng hu = Walden - Thoreau, Henry David 1817-1862 (Shanghai yi wen chu ban she, 2009)
Ben shu ji zai le suo luo zai wa er deng hu pan liang nian you liang ge yue de du ju sheng huo, Shi dang dai mei guo du zhe zui duo de san wen jing dian, Qi hui gui ben xin, Qin jin zi ran de si xiang wei mei guo nai zhi zheng ge shi jie dai lai le qing xin zhi feng
Translation of: Walden / Henry David Thoreau. Published by The Morden Library, ©1937
Keywords: Wilderness areas / Massachusetts / Walden Woods; Natural history / Massachusetts / Walden Woods; Authors, American / 19th century / Biography; Réserves de la vie sauvage / Massachusetts / Walden Woods; Sciences naturelles / Massachusetts / Walden Woods; Écrivains américains / 19e siècle / Biographies; Authors, American; Natural history; Wilderness areas; Massachusetts / Walden Woods; Fiktionale Darstellung